The Science of Biomimetics: Imitating Nature for Almost Natural Solutions - Jain, Avinash; Choudhary, Ekta (Journal of Neonatal Surgery, 2025)
Biomimetics is a scientific discipline that explores the elegant designs found in nature. It has been effectively applied in renowned projects such as the Eiffel Tower, which was inspired by the trabecular structure of bone. In dentistry, the use of biomimetic concepts and protocols aims to preserve tooth structure and vitality, extend the lifespan of dental restorations, and prevent future retreatments. Biomimetic dental materials are naturally biocompatible and possess excellent physical and chemical properties. They have been successfully utilized in various dental fields, providing benefits such as increased strength, sealing, regenerative ability, and antibacterial properties. Many biomimetic materials have also overcome significant limitations of earlier generations of materials. Therefore, this review article aims to shed light on recent developments in the emerging field of biomimetics, specifically in restorative and regenerative dentistry. The review covers different approaches to restoring, remineralizing, and regenerating teeth, as well as various biomimetic dental restorative and tissue engineering materials.